URGENSI PENDIDIKAN AGAMA ISLAM PADA TINGKAT MENENGAH SEBAGAI ALTERNATIF PENDIDIKAN MORAL ANAK BANGSA - M Muizuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
This articles explains about the urgency of islamic education at the senior hight school. We where know own that moral is the most important element that must be carried and instilled by all humans, all religions in the world agree that moral is one of the universal things. Human goodness is not only seen from obedience in carrying out the commands of religion, but moral is one thing that is related to one another, and usually called social. Islamic is a religion that is very guarding the elements that are social and mutual respect with one another. Therefore we offer the concept of Islamic religious education as an alternative to the nation's moral declineKata kunci: Islamic Education, Moral Education